Polish Foreign Policy towards Small East-Central European Countries (1989–2009) (Economic and Political Thought, 2010)
The present article is a thorough politological analysis of the contemporaryinternational relations. It is aimed at presenting and attempting to assessPolish foreign policy in the years 1989 – 2009, giving special considerationto the policy towards small East-Central European countries, i.e. closer andfurther neighbors of Poland. Showing successes and failures of Polish foreignpolicy in the years 1989 – 2009, the author tries to answer the question aboutthe new Polish foreign policy strategy after 2004, i.e. after its accession tothe European Union. He proposes many interesting theses, including onethat Poland, as a medium size country with its demographic, economic andmilitary potential, could successfully play a role of a leader in East-CentralEurope, or even function as a regional superpower gathering around it suchcountries as Lithuania, Latvia, Estonia, the Czech Republic, Slovakia andeven Hungary, Slovenia, Romania and Bulgaria, as well as Scandinavian countries.Taking into account the changing power order at the internationalarena at the beginning of the 21st century and the development of a new,multi-polarized international order, the author suggests that apart from theco-operation with the small countries of the region, Polish foreign policyshould be based on the following assumptions: firstly, the European Unionmust be a foundation stone of Polish foreign policy; secondly, NATO mustbe the foundation for Polish security policy; thirdly, Poland should developco-operation and versatile relations with the United States but it should notsupport those aspects of American foreign and security policy which do notserve the interests of the West, nor international stability, and question UN’scredibility and are aimed at creating divisions in Europe and the world.The author used such research methods as an analysis of documents andinternational processes and a diagnostic comparative method.